Business Remodeling in Small Medium Enterprises in the Digital Era: Systematic Literature Review - Arum Arupi Kusnindar (Sekolah Tinggi Ilmu Ekonomi AMM, 2022)
This study aims to examine changes in the business model of SMEs in Indonesia with digital transformation as a determinant variable. This research is expected to be able to answer research questions, namely what are the focus of research on business models that have been carried out, the relationship between research focuses and how the methodologies and approaches are carried out. The three research questions are expected to answer the fourth research question, namely how the business model changes in the SME sector. The research method uses a systematic literature review of journals published through Scopus and Google Scholar. The results show that the focus of research on business models is mostly related to digitalization, business model concepts, innovation and business processes. There was a tendency to use mixed methods and quantitative methods after 2000. Previously, research on business models was mostly done using literature reviews, comprehensive journal reviews and case studies. Changes in business models in SMEs cannot be known because of the lack of research related to changes in business models in SMEs.